Taxonomic revision of the genus Punjuba (Leguminosae, Caesalpinioideae) - Soares, Marcos Vinicius Batista; Guerra, Ethiéne; Morim, Marli Pires; Iganci, João Ricardo Vieira (Phytotaxa, 2024)
Punjuba is a Neotropical genus of the mimosoid clade (Leguminosae). The genus was recently restablished and is recognized by presenting shrubs and trees, with lax racemes or spiciform racemes, leaves with 1–3 pairs of pinnae and 2–7 pairs of leaflets in each pinna, thin and lateraly compressed legumes, curved to spiral, and seeds lacking pleurogram. Recent advances on legumes systematics have been producing great challenges on the circumscription of genera, especially on the mimosoid clade. Molecular phylogenetic studies confirm that Punjuba is monophyletic, and a revision of the genus and species circumscriptions are needed. Here we present a taxonomic revision of Punjuba, providing an identification key for all species currently recognized in the genus, morphological descriptions, and distribution maps. We recognize six species in the genus: P. callejasii, P. centiflora, P. killipii, P. lehmannii, P. racemiflora and P. foreroana, being the last one described here as a new species. Abarema josephi is proposed as a new synonym of P. lehmannii. Morphological characters including the inflorescence, indumentum, leaves and leaflets, besides quantitative characters, were applied as diagnostic to recognize the species.